Penerapan Metode Human Centered Design dalam Perancangan Layanan Psikologi Bagi Mahasiswa Fakultas Sains dan Teknologi - Madhan, Rahmat Ramadhan; Akib, Faisal; Wahyuni, Sri (Prodi Teknik Informatika Universitas Islam Negeri Makassar, 2024)
The Human Centered Design method is a method used to better understand the user's comfort and convenience in using a service. In this research, the case study for applying this method is psychology services for students of the Faculty of Science and Technology. This method is usually used in creating UI/UX designs to help designers get to know users better through the level of comfort and convenience that users want when using the services they create. This research aims to apply and test whether the Human Centered Design method is good or not in designing psychological services. It is hoped that the implementation of the Human Centered Design method will be able to test whether this method is suitable for use in designing psychological services for Faculty of Science and Technology students. It is hoped that the results of this research will become new knowledge regarding the application of the Human Centered Design method in case studies of psychological services for students of the Faculty of Science and Technology and can be applied in other case studies.